A COMPARATIVE STUDY OF VOCABULARY BETWEEN ACEHNESE AND MALAY PATANI LANGUAGE - Yosua Septianda Gea; Zulvia Safriani; Irfan Sau; Rauzatul Jannah; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The main objective of this study is the vocabulary comparison betweenthe Acehnese and Patani languages. The purpose of this study is to: (1)to find out the equal meaning of the same vocabulary between Acehneseand Melayu Patani language; and (2) know the similarity of vocabularywith different meanings between Acehnese and Melayu Patani language.Since this study aimed to describe the difference and the similarity ofmeaning between Acehnese and Melayu Patani language vocabulary, theauthors chose to use a descriptive qualitative method. The participants ofthis study were 2 students of Acehnese and a Patanian of EnglishEducation Program Study at Bina Bangsa Getsempena University. Thedata were collected through observation and a depth interview. Theresults of this study consisted of 53 comparison vocabularies thatcontained 41 equations between Malay Patani and Aceh languagevocabularies with the same meaning and 12 equations of Malay Pataniand Aceh language vocabularies with different meanings.